2018
DOI: 10.15406/mojap.2018.05.00159
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic Index in Sexual Dimorphism and Racial Diversity: A Mini Review

Abstract: Recent years have seen significant advances in the field of anatomical pedagogy. Among these major advances, the introduction of clinical reasoning in the early years of the medical curriculum has modified and modernized the approach to teaching anatomy. At the Faculty of Medicine of the Gaston Berger University of Saint-Louis, conventional high-school teaching has been enriched by this new teaching method.Clinical reasoning is the foundation of medical practice, it brings together processes of thought and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…In a term paper review by Orish C N on works by various authors, both abroad and Indian, higher values were cited for male parameters compared to female ones in an Indian study; the paper revealed that cranial index and dimensions would tend to vary with sexes. 12 In Setiya et al study, females showed a higher mean cranial index compared to males, with somewhat similar results as shown in our study. They got their mean cranial index for male and female as respectively 77.65 ± 3.34 and 78.13 ± 3.76 with a higher sample size of 140 dry human skulls.…”
Section: Discussionsupporting
confidence: 91%
“…In a term paper review by Orish C N on works by various authors, both abroad and Indian, higher values were cited for male parameters compared to female ones in an Indian study; the paper revealed that cranial index and dimensions would tend to vary with sexes. 12 In Setiya et al study, females showed a higher mean cranial index compared to males, with somewhat similar results as shown in our study. They got their mean cranial index for male and female as respectively 77.65 ± 3.34 and 78.13 ± 3.76 with a higher sample size of 140 dry human skulls.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning gender, no significant difference could be identified between the participants from South India and North East India. This result contradicts with the previousfindings that showed sex or gender difference 1,9 .…”
Section: Not Significantcontrasting
confidence: 99%
“…Studies indicate the relevance of the cephalic index to identify racial, ethnic, and gender differences. Findings related to cephalic index and head shape benefits the area of forensic science and forensic anthropologyimmensely, which includes facial reconstruction of disputed identity 7 , determination 8 and classification 9 of race and sex, and identification of an anonymous individual's geographical region 10 .…”
Section: Introductionmentioning
confidence: 99%
“…CI can slightly change with growth, and the normal CI range may vary depending on patient's ethnicity. 22 CVAI 18 is usually used to classify plagiocephaly. The Children's Healthcare of Atlanta scale defines plagiocephaly as mild when the CVAI is 3.5-6.25, moderate when the CVAI is 6.25-8.75, severe when the CVAI 8.75-11, and very severe when greater than 11.…”
Section: Discussionmentioning
confidence: 99%